Les Intoxications Accidentelles Par Les Pesticides Au Maroc Entre 2008-2014: Evolution Et Facteurs De Risque - Aicha, Detsouli; Amiar, Latifa; Zineb, Nabih; Donia, Kharbouch; Zakaria, Abidli; Maria, Windy; Naima, Rhalem; Abdelmajid, Soulaymani; Abdelrhani, Mokhtari; Rachida, Soulaymani- Bencheikh (European Scientific Journal, ESJ, 2017)
The aim of this study was to determine the epidemiological profile of accidental poisoning by pesticides. A retrospective study of poisoning cases, declared between January 2008 to December 2014 at the Moroccan Anti poisoning and Pharmacovigilance Center (MAPPC), was conducted. During the study period, 4 110 acute accidental poisoning by pesticides cases were collected. The average age was of patients 19, 24±0,25 years. The sex-ratio (female/male) was 0.95. Poisoning mainly concerned adults between the ages of 20 and 74 (about 43%). The pesticide poisoning occurs more often in urban zones with 54.1%. These were mainly poisonings that occurred at home in 70.5% of cases. Patients were mostly symptomatic (about 65%), these poisonings occurred mainly during the spring mostly in the spring (32%) and summer (29%). Insecticides were the most commonly incriminated in 64, 13% of cases, followed by rats, pesticides, and herbicides with respectively 29%, 3.42% and 0.85%. The declarations came from all regions of Morocco, the highest incidence was recorded in the Tadla-Azilal region (4.04 per 100 000 inhabitants). The Fes Boulemane region showed a significant lethality of 6.43%. Among the 3,077 patients for whom the evolution was known, 98.1% had progressed favorably. 47 cases of death were recorded with a lethality of 1.2%.